Determinan yang Mempengaruhi Capaian Penerimaan Retribusi Daerah Provinsi Kalimantan Selatan - Ferina, Adya; Adriani, Ade; Suhaili, Achmad (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2021)
This study examines the influence of (1) the relationship between leadership commitment on the retribution receivable; (2) the relationship between supervison on the retribution receivable; (3) the relationship between human resources on the retribution receivables; (4) the relationship between regulation on the retribution receivables in south borneo government.Data collection resulted from thirty eight local government head of personal division retribution in south borneo province. Multiple Regression Analysis as the data analysis method.The results of study showed prove that human resources have a positive effect on the achievement of retribution receipts, while leadership commitment, supervision and the regulatory system have no effect on the achievement of retribution receipts. This means that the more quality the human resources in the SKPD, the higher the achievement of retribution receipts. For the SKPD, this means that SKPD must always improve the quality of human resources in the SKPD by providing education, training, as well as giving awards and clear and firm sanctions.